Penerapan SOP Bagi Mahasiswa PKL Pada Departemen Food And Beverage Service The Oberoi Beach Resort, Bali - Ida Ayu Putu Padma Sri Wahyuni Wahyuni; I Putu Gede Parma (Jurnal Manajemen Perhotelan dan Pariwisata, 2020)
This study aims to explore (1). The SOP delivery process for intern students in the Food and Beverage Service department (2). The implementation of SOPs by intern students in the Food and Beverage Service Department. This research was a qualitative descriptive research, with interview method and documentation in data collection. The subjects in this study were HRD staff and seniors in the room service section at The Oberoi Beach Resort, Bali. The results showed that (1). The process of delivering SOP for internship students was done by providing material during pre training, role play training and delivering SOP 15 minutes prior to new shift. (2). The SOP was delivered in the form of briefing and training for trainees. From the results of this study it may be necessary to further research on the importance of understanding SOP for intern students in a broader scope